Pedagogical problems for a reflective teacher Practicum - Saiz Linares, Ángela; Susinos Rada, Teresa (Revista Complutense de Educación, 2017)
The practicum in teacher training has emerged in recent years as one of the cardinal elements in redefining the teacher initial training. Several studies highlight the need to base these programs in reflective and collaborative models. In this article we present a practicum proposal articulated as a work of inquiry and reflection that unfolds from the educational problems that pupils identify as relevant. More specifically, we analyze the five projects of inquiry developed by the students in order to discover: their pedagogical interests related to their placements, the focus of reflection in their initial formulations and the vision of education and teaching that can be inferred and, finally, some relationships between the pedagogical concerns of the students and their personal and school biography. For this study we used a qualitative methodology framed in the evaluative case study. The data analysis comes from the information produced in a semi-structured interview and the student diaries. The results presented show the influence of the placement schools in shaping the students’ perceptions of teaching, a preference for a technical and a practical paradigm of teaching and the importance of family and school experiences in the interpretation that the students do of their teaching experiences.
Keywords: Teacher training; school placement; reflective practice; inquiry on teacher practice